Population‐specific frequencies for LRRK2 susceptibility variants in the genetic epidemiology of Parkinson's disease (GEO‐PD) consortium. Issue 12 (2nd August 2013) - Heckman, Michael G.; Soto‐Ortolaza, Alexandra I.; Aasly, Jan O.; Abahuni, Nadine; Annesi, Grazia; Bacon, Justin A.; Bardien, Soraya; Bozi, Maria; Brice, Alexis; Brighina, Laura; Carr, Jonathan; Chartier‐Harlin, Marie‐Christine; et al.
ABSTRACT Background Variants within the leucine‐rich repeat kinase 2 gene are recognized as the most frequent genetic cause of Parkinson's disease. Leucine‐rich repeat kinase 2 variation related to disease susceptibility displays many features that reflect the nature of complex, late‐onset sporadic disorders like Parkinson's disease. Methods The Genetic Epidemiology of Parkinson's Disease Consortium recently performed the largest genetic association study for variants in the leucine‐rich repeat kinase 2 gene across 23 different sites in 15 countries. Results Herein, we detail the allele frequencies for the novel risk factors (p.A419V and p.M1646T) and the protective haplotype (p.N551K‐R1398H‐K1423K) nominated in the original publication. Simple population allele frequencies not only can provide insight into the clinical relevance of specific variants but also can help genetically define patient groups. Conclusions Establishing individual patient‐based genomic susceptibility profiles that incorporate both risk factors and protective factors will determine future diagnostic and treatment strategies. © 2013 International Parkinson and Movement Disorder Society